Pengaruh Tingkat Pendidikan dan Motivasi Kerja terhadap Kinerja Pegawai Dinas Sosial Provinsi Sulawesi Selatan - Julian, Endri (Patria Artha University, 2018)
This study aims to determine and analyze the effect of the level of education and work motivation on employees of the South Sulawesi Provincial Social Service.This study was carried out using a quantitative descriptive approach to obtain a complete picture of the variables studied. This type of survey research is analyzing the data needed to support the discussion of research in solving and answering the problems that have been formulated. Data analysis used in this research is Multiple Linear Regression.Based on the results of this study prove the constant (b0) = 0.590, which indicates that if there is no level of education and work motivation, then the employee's performance will be constant, which is 0.590. The value of b1 = -0.31 shows that the education level variable does not have a positive effect on the performance variable. Thus the current employee performance is not influenced by the educational background or level of education available. This is further strengthened by the value of standardized coefficient which is also negative. Value of b2 = 0.846 indicates that work motivation contributes positively to performance. This means that the better the work motivation given, the better the employee's performance will be. The magnitude of the effect of work motivation variables can be seen again from the value of the standardized coefficient that is equal to 0.583 or in other words the work motivation gives an effect on performance of 58.3%.